PARTISIPASI MASYARAKAT DALAM PENGADAAN AIR MINUM DI JALUR PANTURA - Nurul Akhmad (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
The background of the research is the researcher curiosity to know people participation in some villages in Sayung Sub-district, which border on South coast in water supply and management. Although there is no water supply from Sayung Sub-district government, there is no social movement in the area. The research focuses on the background, problems, and efforts in people participation application to supply water in villages in Sayung Sub-district i.e. Bedono, Timbulsloko, Surodadi, and Sriwulan. The results of the research are, first, the background of people participation in supplying water is the need of water as the primary need for life. Second, people participation in water supply and management consists of physic and non-physic. Non-physic includes ideas while. physics includes money collecting to buy and maintain water pump and working together to install water pipes. Third, the effort to encourage people participation in water supply is by empowering people participation by people's figures, religion figures and education party. The conclusion of the research is that although people participation in Bedono, Timbulsloko, Surodadi, and Sriwulan - villages in Sayung Sub-district in water supply and management is good, but it is necessary to apply better technology to change the use of artesian wells. From the conclusion, the researcher recommends first, the government needs to do preliminary and quality test on the water from artesian wells. Second, before the government is able to supply water to those villages, the government needs to give subsiding by reducing the price of electricity bill, especially which is used for water pump from artesian wells which are used for public.